2018
DOI: 10.1017/wet.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Likelihood of Residual Herbicide Carryover to Cover Crops

Abstract: Research was conducted to evaluate the sensitivity of cover crops to a low rate of soil-applied herbicides and investigate the likelihood of herbicide carryover to fall-seeded cover crops following an irrigated corn crop. In the sensitivity study, herbicides were applied at a 1/16×rate (to simulate four half-lives) 1 d after cover crop planting, whereas for the carryover study residual herbicides were applied at a 2×rate at the maximum label corn height or growth stage and cover crops sown immediately after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 28 publications
6
39
2
Order By: Relevance
“…Cornelius and Bradley (2017) reported biomass reductions from herbicide carryover onto wheat, forage radish, cereal rye, crimson clover, oats, Austrian winter pea, annual ryegrass, and hairy vetch. Palhano et al (2018) observed results similar to what we found, with no biomass reduction of Austrian winter pea, cereal rye, wheat, hairy vetch, or rapeseed, but they did observe a biomass reduction of crimson clover from atrazine, pendimethalin, pyroxasulfone, and S-metolachlor. Differences between our findings and the results from this previous research are most likely due to differences in the environmental and soil conditions in Virginia compared with those of Arkansas and Missouri.…”
Section: Cover Crop Biomass Responsesupporting
confidence: 90%
See 2 more Smart Citations
“…Cornelius and Bradley (2017) reported biomass reductions from herbicide carryover onto wheat, forage radish, cereal rye, crimson clover, oats, Austrian winter pea, annual ryegrass, and hairy vetch. Palhano et al (2018) observed results similar to what we found, with no biomass reduction of Austrian winter pea, cereal rye, wheat, hairy vetch, or rapeseed, but they did observe a biomass reduction of crimson clover from atrazine, pendimethalin, pyroxasulfone, and S-metolachlor. Differences between our findings and the results from this previous research are most likely due to differences in the environmental and soil conditions in Virginia compared with those of Arkansas and Missouri.…”
Section: Cover Crop Biomass Responsesupporting
confidence: 90%
“…Treatments containing imazethapyr, fomesafen, and flumetsulam resulted in the greatest herbicide carryover symptoms across all cover crop species evaluated (Cornelius and Bradley 2017). In Arkansas, Palhano et al (2018) observed carryover injury on crimson clover from atrazine, pendimethalin, pyroxasulfone, and S-metolachlor, and on cereal rye and wheat from pyroxasulfone. Other research indicates that atrazine and metsulfuron injured wheat a year after it was applied (Moyer et al 2010).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…20,22 Another concern regarding atrazine application is the residual effect of the herbicide in susceptible succession crops. 23 For example, maize and soybean rotation is a common practice in several regions around the world, 24 and atrazine applied for weed control during maize cultivation has been shown to negatively affect the subsequent development of soybean plants in the same area. 25 It is therefore of great relevance to evaluate how atrazine nanoencapsulation would affect the residual herbicidal effect on a susceptible crop.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the sensitivity of crops to the carryover effect of atrazine, which significantly reduces vetch, clover and bean biomass, and minimizes the emergence of barley and oats by 20% and 16%, respectively (Palhano et al, 2018). Sunflower (Helianthus annuus L.) is also sensitive when sown shortly after application of atrazine to the predecessor crop (Brighenti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%